Acute pancreatitis- a narrative review - Zahabia Sohail; Shaikh, Hafsa; Nimra Iqbal; Om Parkash (Journal of the Pakistan Medical Association, 2024)
Acute pancreatitis is a common cause of acute abdominal pain and can range from mild oedema to severe necrosis of the pancreas. It has a significant impact on morbidity, mortality and financial burden. The global prevalence of pancreatitis is substantial, with the highest rates observed in central and eastern Europe. Diagnosing acute pancreatitis involves considering clinical symptoms, elevated serum amylase and/or lipase levels, and characteristic imaging findings. The causes of acute pancreatitis include obstructive disorders, such as gallstones and biliary sludge, alcohol consumption, smoking, drug-induced pancreatitis, metabolic disorders, trauma, medical procedures, infections, vascular diseases and autoimmune pancreatitis. Appropriate management of acute pancreatitis involves determining the severity of the condition, providing supportive care, addressing the underlying cause, and preventing complications. Advances in classifying the severity of acute pancreatitis and implementing goal-directed therapy have contributed to a decrease in mortality rates. ---Continue